2020
DOI: 10.1080/10810730.2020.1825568
|View full text |Cite
|
Sign up to set email alerts
|

Youth’s Proximity to Marijuana Retailers and Advertisements: Factors Associated with Washington State Adolescents’ Intentions to Use Marijuana

Abstract: The current study explored the influences of advertising exposure, numbers of marijuana retailers, distance to retailers, and constructs from the integrative model of behavioral prediction, including outcome beliefs, perceived norms, and efficacy, on youth's intentions to use marijuana in a state in which the use of recreational marijuana is legal. A statewide online cross-sectional survey of 350 adolescents ages 13-17, residing in Washington state, was conducted in June 2018. The results of the regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…First, most studies assessed data at aggregate level (zip-code, city, county, etc. ), because detailed addresses of individuals were often unavailable [7,[12][13][14][15][16][17][18][19][22][23][24][25]. Such studies were unable to control for heterogeneities among individuals or account for the fact that dispensaries located in close proximity have larger impacts than dispensaries located further away.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, most studies assessed data at aggregate level (zip-code, city, county, etc. ), because detailed addresses of individuals were often unavailable [7,[12][13][14][15][16][17][18][19][22][23][24][25]. Such studies were unable to control for heterogeneities among individuals or account for the fact that dispensaries located in close proximity have larger impacts than dispensaries located further away.…”
Section: Introductionmentioning
confidence: 99%
“…Fifthly, cannabis marketing in previous research was measured by self-reported exposures [8,23,40,[44][45][46][47], with one exception [21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cannabis dispensary density has been associated with several health and safety outcomes in previous work (Boggess et al 2014;Everson et al 2019;Hust et al 2020;Liang and Shi, 2019;Shi et al 2018). Studies show greater density and availability of medical cannabis dispensaries and recreational stores in areas with lower household incomes (Morrison et al, 2014l Shi et al, 2016, greater percent of racial/ethnic minorities (Hughes et al 2020;Shi et al, 2016;Thomas and Freisthler, 2016a), and greater overall area deprivation (e.g., lower percent owner-occupied housing, higher percent living below poverty level, etc.)…”
mentioning
confidence: 95%